When is a slur not a slur? The use of nigger in 'Pulp Fiction'. (November 2015) - Allan, Keith
Abstract: Slurs are defined and shown to be determined by context of use and not lexical form. It has been proposed that words like nigger should be eradicated from the English language on the presupposition that the word itself is a slur and its eradication will eliminate the slur against African-Americans. This presumption is demonstrably false and in any case eradication of slurs is shown to be an unrealistic goal. In order to understand why nigger counts as a slur, the dysphemistic properties attributed to the word and its typical referents are described. Communities which are the target of a slurring term sometimes adopt that term as a mark of in-group solidarity and camaraderie; this has happened with nigger . It is against this background that I scrutinize the function of each occurrence of the word nigger within the film script of Quentin Tarantino's 'Pulp Fiction'. I closely examine the style of language used within the film script, taking account of other potential slurs, obscenities, and instances of banter and repartee in order to judge if Tarantino uses nigger as a reasonable instrument within the development of a character and/or to make a dramatic point or, instead, whether the word occurs gratuitously in order to shock or cause offense. I conclude that in 'Pulp Fiction' most occurrences of nigger are uttered by one African-American to or about another in the spirit of camaraderie (what Australians would call 'mateship'). Where it is uttered by a white to a black friend it is also of this nature. The two instances where nigger is used by one white to another do show disrespect towards African-Americans but not malice, and they serve to make a dramatic point. Highlights: A distinction is made between words that are potential slurs and their use as slurs. Nigger is not always used derogatorily as a slur. Here nigger is mostly uttered by one black to another in the spirit of camaraderie.